Application of Biodegradable Welding Materials - Madaliyev Samandar Dilshod o’g’li; Abdukarimova Ferishtabonu Azimjonovna; Fazilov Dusmurat Saydivaliyevich (Academia One, 2024)
In the modern world, facing increasing problems of climate change and natural resource depletion, issues of sustainable development and environmental responsibility become an integral part of the activities of industrial enterprises. Industry, including welding production, plays a key role in shaping negative environmental impact through the use of traditional welding materials
Keywords: Application; role; responsibility; integral